Transformasi layanan bimbingan dan konseling di era digital: peluang, tantangan, dan implikasi terhadap pengembangan kompetensi siswa - Jihan Diva Meira; Ni Ketut Suarni; I Ketut Dharsana (JPGI (Jurnal Penelitian Guru Indonesia), 2026)
The digital era has brought fundamental changes in various aspects of life, including the fields of education and guidance and counseling (GC) services. This article comprehensively discusses the transformation of GC services in the digital era, focusing on opportunities, challenges, and their implications for the development of students’ competencies. Through a systematic literature review and synthesis of various recent studies published in SINTA-indexed journals, it was found that digitalization enables the expansion of GC service access through online platforms, the development of interactive media, and greater efficiency in counseling administration. However, this transformation also faces challenges such as counselors’ digital competency readiness, infrastructure limitations, and ethical and privacy issues. The study also reveals that research on cybercounseling in Indonesia still requires further development, particularly regarding service effectiveness and interdisciplinary collaboration. The implications of this transformation highlight the need to redefine the counselor’s role, strengthen ethical frameworks for technology-based services, and develop hybrid service models that are responsive to the needs of the digital generation. This article contributes to enriching the discourse on the development of the guidance and counseling profession in Indonesia so that it remains responsive to contemporary developments while upholding humanistic values